Saponin rich tropical fruits affect fermentation and methanogenesis in faunated and defaunated rumen fluid - Hess, H.D.; Kreuzer, M.; Díaz, T.E.; Lascano Aguilar, Carlos Eduardo; Carulla, Juan E.; Soliva, CR; Machmuller, A (2003)
A comparison of the effects on rumen fermentation of three saponin rich tropical fruits supplemented to forage-based diets was completed using a rumen simulation technique (Rusitec). The diets contained either no tropical fruit or 100?mg/g of Sapindus saponaria (crude saponins, 120?mg/g), 200?mg/g of Enterolobium cyclocarpum (crude saponins, 19?mg/g) or 200?mg/g of Pithecellobium saman (crude saponins, 17?mg/g). The four diets were evaluated with faunated and defaunated rumen fluid obtained from a single donor cow. Compared to the control diet, P. saman decreased (P<0.05) ammonia concentration of rumen fluid, and E. cyclocarpum and P. saman increased (P<0.05) n-butyrate proportion of total volatile fatty acids. Defaunation enhanced (P<0.05) propionate proportion with corresponding reductions of acetate and n-butyrate. Organic matter degradation of the S. saponaria diet did not differ from that of the control diet but was higher (P<0.05) with P. saman and E. cyclocarpum. Only one of the saponin rich fruits evaluated, S. saponaria, decreased (P<0.05) protozoal count (by 54%) and daily methane release (by 20%) relative to control, but without affecting the methanogen count. Defaunation suppressed methanogenesis by 43% over all diets (P<0.05), and the effect of S. saponaria on methane was more pronounced in defaunated (29%) versus faunated rumen fluid (14%). When related to organic matter apparently fermented, differences relative to the control diet persisted (P<0.05), but methane release per unit of fibre degraded did not differ between the S. saponaria diet and the control diet. This study demonstrated that supplementation with S. saponaria is effective against ruminal methanogenesis, but that this was not exclusively an effect of the associated depression in protozoal count.